2012
DOI: 10.1159/000334660
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Catecholamine Levels as Predictors of Outcome in Subarachnoid Hemorrhage

Abstract: Objective: Subarachnoid hemorrhage (SAH) is associated with marked sympathetic activation at the time of ictus. The purpose of this study is to determine whether early central catecholamine levels measured from cerebrospinal fluid (CSF) relate to outcome in patients with SAH. Methods: Observational study of consecutive SAH grade 3–5 patients who underwent ventriculostomy placement, but did not undergo open craniotomy for aneurysm obliteration. CSF samples were obtained during the first 48 h following symptom o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 104 publications
0
18
0
Order By: Relevance
“…Moussouttas et al (2012) and Dilraj et al (1992) demonstrated that plasma and CSF levels of epinephrine are independent predictors of morbidity and mortality in SAH. Although epinephrine detection assays of blood and urine are well-developed and simplistic, epinephrine should be combined with other markers of disease to increase sensitivity and specificity for SAH.…”
Section: Discussionmentioning
confidence: 99%
“…Moussouttas et al (2012) and Dilraj et al (1992) demonstrated that plasma and CSF levels of epinephrine are independent predictors of morbidity and mortality in SAH. Although epinephrine detection assays of blood and urine are well-developed and simplistic, epinephrine should be combined with other markers of disease to increase sensitivity and specificity for SAH.…”
Section: Discussionmentioning
confidence: 99%
“…Increased sympathetic activation, which has been observed in patients with spontaneous SAH and poor outcome, may directly influence ANP release [27]. In addition to neurohumoral effects, ANP increase may be triggered by therapeutic regulation of fluid balance and systemic vascular resistance [5].…”
Section: Discussionmentioning
confidence: 99%
“…The role of biomarkers for evaluation has not been studied in large cohorts. Small studies suggest that catecholamine levels in cerebrospinal fluid (CSF) are elevated in patients who experience early mortality or disability [28]. Serum S100 has been associated with poor outcome after SAH [29].…”
Section: Aneurysmal Sah – Ruptured Aneurysm (Ria)mentioning
confidence: 99%